2020
DOI: 10.1007/s10461-020-03072-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Oral Pre-exposure Prophylaxis (PrEP) Among Women from Durban, South Africa as Part of the HIV Prevention Package in a Clinical Trial

Abstract: HIV endpoint-driven clinical trials in Africa enroll women who are at heightened risk of acquiring HIV. In 2017, the South African Medical Research Council recommended the provision of oral pre-exposure prophylaxis (PrEP) in HIV prevention trials, at which time the Evidence for Contraceptive Options and HIV Outcomes trial was ongoing and began to provide PrEP on-site at some trial sites. We interviewed 132 women who initiated PrEP on-site at the Durban, South Africa trial site to explore PrEP use, and conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…Self-reported adherence to oral PrEP was collected over the prior 30 days among women who reported ongoing oral PrEP use (had used oral PrEP within the prior 30 days) at the time of the questionnaire. As previously reported, 37% of women reported no missed doses in the prior 30 days [17].…”
Section: Oral Prep Adherencesupporting
confidence: 77%
See 1 more Smart Citation
“…Self-reported adherence to oral PrEP was collected over the prior 30 days among women who reported ongoing oral PrEP use (had used oral PrEP within the prior 30 days) at the time of the questionnaire. As previously reported, 37% of women reported no missed doses in the prior 30 days [17].…”
Section: Oral Prep Adherencesupporting
confidence: 77%
“…Women who disclosed oral PrEP use continued oral PrEP more than those who did not disclose, whilst women who reported having more than one sexual partner and those who felt that they had a high risk of HIV infection had reduced odds of continuing oral PrEP at the final study visit. As reported previously, 43% of women who were eligible for oral PrEP when it became available, had initiated oral PrEP onsite [17]. We found that the proportion of women continuing oral PrEP at month 1 and month 3 in our study was higher than in some studies conducted among AGYW in South Africa and Kenya [8,10] such as the DREAMS study in Kenya, where only 37% of AGYW who initiated oral PrEP, persisted with PrEP use at month 3 [8].…”
Section: Discussionsupporting
confidence: 65%
“…In our study, we found that all women had disclosed PrEP use, and most women disclosed to their partners. Disclosure of PrEP use has varied in recent studies, for example in HPTN082, only 40% of women planned to disclose PrEP use [ 24 ], while in the ECHO trial, at one research site, 90% of women had disclosed PrEP use [ 25 ]. Reasons for high rates of disclosure among our study participants might be because women in our study were older, pregnant, and reported close, supportive relationships with family members and partners, which might be different to other populations such as adolescent girls and young women.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of integration has been demonstrated within this ECHO study experience and other studies (5,20,21). The first step in the implementation of PrEP at KHC is representative of strong political will.…”
Section: Discussionmentioning
confidence: 65%